(untitled) (Journal of Universal Science Research, 2023)
Translation is the process of converting a text from one language to another. It is a complex task that requires a deep understanding of grammar, syntax, vocabulary, and cultural nuances. One of the biggest challenges faced by translators is dealing with grammar problems. This article discusses some of the most common grammar problems encountered during translation and provides solutions to overcome them.